2016
DOI: 10.1111/acv.12323
|View full text |Cite
|
Sign up to set email alerts
|

Biologgers reveal post‐release behavioural impairments of freshwater turtles following interactions with fishing nets

Abstract: Bycatch, the incidental capture of non-target organisms, occurs in most commercial fisheries. Although immediate bycatch mortality is frequently documented in fisheries, detrimental sub-lethal effects and potential post-release mortality remain largely unknown despite the potential population-level consequences. Turtles are captured as bycatch and their populations are vulnerable to slight increases in adult mortality. In eastern Ontario, turtles are frequently captured as bycatch in a smallscale freshwater co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These expectations are particularly well suited to testing in the wild with acceleration telemetry (e.g., Cooke et al., ; Cruz‐Font, Shuter, & Blanchfield, ), and our objective in this study was to carry out such a test by: (a) generating extended (~20 days), temporally fine scale (~10 min) direct measures (i.e., the frequency of resting periods and the intensity of activity during active periods) of the feeding activity of an apex visual predator during a critical period in its annual growing season; (b) comparing those measures across populations that differ greatly in both the size and accessibility of available prey. Acceleration telemetry has been used in much recent work to assess the short‐term impact on fish behaviour of various anthropogenic manipulations (e.g., fisheries capture—Gutowsky et al., ; light pollution—Foster, Algera, Brownscombe, Zolderdo, & Cooke, ). Our study is one of only a few so far reported (e.g., Brownscombe, Cooke, & Danylchuk, ) that uses acceleration telemetry to generate cross‐population comparative data designed to address a question of fundamental ecological interest.…”
Section: Introductionmentioning
confidence: 99%
“…These expectations are particularly well suited to testing in the wild with acceleration telemetry (e.g., Cooke et al., ; Cruz‐Font, Shuter, & Blanchfield, ), and our objective in this study was to carry out such a test by: (a) generating extended (~20 days), temporally fine scale (~10 min) direct measures (i.e., the frequency of resting periods and the intensity of activity during active periods) of the feeding activity of an apex visual predator during a critical period in its annual growing season; (b) comparing those measures across populations that differ greatly in both the size and accessibility of available prey. Acceleration telemetry has been used in much recent work to assess the short‐term impact on fish behaviour of various anthropogenic manipulations (e.g., fisheries capture—Gutowsky et al., ; light pollution—Foster, Algera, Brownscombe, Zolderdo, & Cooke, ). Our study is one of only a few so far reported (e.g., Brownscombe, Cooke, & Danylchuk, ) that uses acceleration telemetry to generate cross‐population comparative data designed to address a question of fundamental ecological interest.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from sub‐lethal impairment, post‐release mortality and altered behaviour may potentially be an issue with turtles after being submerged in nets. Gutowsky et al (2017) assessed post‐release behaviour and survival using biologgers with painted and eastern musk turtles from two treatment groups (entrapment for 4 hours and a control). No post‐release mortality was observed.…”
Section: Body Of Researchmentioning
confidence: 99%
“…Most commonly, biotelemeters have been used to link field metabolic rates with movement patterns, and sometimes with feeding behaviours ( Cooke et al , 2004 ; Homyack, 2010 ). However, contributors to ‘Conservation Physiology’ have begun, in an array of taxa, much more subtle applications that are capable of assessing the impact of capture on physiological stress and survivorship of individuals and their movement patterns ( French et al , 2015 ; Gutowsky et al , 2017 ). Critically, this approach takes existing technology and applies it so that physiological traits can be measured—sometimes for the first time—and results can be used to advise management of threatened species.…”
Section: Technological Boundariesmentioning
confidence: 99%